2021
DOI: 10.13107/jocr.2021.v11.i08.2346
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Bilateral Asymmetrical Traumatic Hip Dislocation – A Rare Presentation

Abstract: Introduction: Asymmetric bilateral hip dislocations are very rarely reported in literature. We report a unique case of asymmetric traumatic bilateral hip dislocation in a 34-year-old male, describing the management and post-operative complications. Case Report:A 34-year-old truck driver sustained injury to both his hips in a head on collision between two trucks while seated in the passenger seat. There was a delay in presentation at our institution as he was referred after 17 h of the trauma. After evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
4

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 9 publications
0
6
0
4
Order By: Relevance
“…3 As in symmetrical bilateral or unilateral dislocations, they are also associated with a better prognosis when the reduction is performed within 6 hours of the trauma. 2 Regarding outcomes, 61% of patients with asymmetric hip dislocations returned to normal strength, absence of pain and full range of motion (ROM) while 31% evolved with mild pain, small change in ROM or some non-damaging loss of strength. The remainder of patients developed impairment or changes in lifestyle due to long-term complications, generally found in patients with multiple injuries.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…3 As in symmetrical bilateral or unilateral dislocations, they are also associated with a better prognosis when the reduction is performed within 6 hours of the trauma. 2 Regarding outcomes, 61% of patients with asymmetric hip dislocations returned to normal strength, absence of pain and full range of motion (ROM) while 31% evolved with mild pain, small change in ROM or some non-damaging loss of strength. The remainder of patients developed impairment or changes in lifestyle due to long-term complications, generally found in patients with multiple injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The first reported case of bone exposure was described in 2023 by Santoso et al 8 Associated fractures were reported in 44% of patients, with acetabulum fracture accounting for 75% of these fractures. 2 Negligence in asymmetric hip dislocation is considered when the dislocation time is more than 1 week. 9 The treatment of neglected hip dislocations is complex, due to the formation of fibrous tissues in the joint.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations